Analysis of Service Quality, Ship Rental Prices, and Ship Management Influence on Charterer Loyalty Satisfaction and Impact at PT Buana Lintas Lautan Tbk. - Muhammad Muflih Alfian (Journal of Social Science, 2022)
This study aims to analyze the effect of service quality, ship charter prices and ship management on customer satisfaction and customer loyalty or commonly called charterers, by the shipping company world. The research sample was 200 people from charterers or customers from PT. Buana Lintas Lautan Tbk. The data were collected using a questionnaire and Structural Equation Modeling (SEM) as an analytical technique using the AMOS 22 program. The study results prove that service quality, ship charter prices and ship management have a positive and significant impact on customer satisfaction and customer loyalty. The results of this study have implications for service quality, ship rental prices and ship management, which need to be improved to increase customer satisfaction and loyalty.